Physical and Mechanical Analysis of Vegan Leather Reinforced with Natural Fiber - Zahari, Intan Nur Zalikha; Mohd Nazrul Roslan, (Progress in Engineering Application and Technology, 2026)
This study addresses the environmental and ethical issues associated with conventional animal leather and synthetic vegan leather by developing a sustainable plant-based alternative reinforced with natural fibers. The objective of this research is to fabricate and evaluate vegan leather using pineapple leaf fiber, banana stem fiber, and bamboo fiber with a natural latex binder. Non-woven mats were produced through a needle punching process and subsequently impregnated with latex using the vacuum infusion technique. The fabricated vegan leather composites were evaluated for physical properties including density, thickness, and hardness, as well as mechanical properties through tensile and tearing tests in accordance with ISO 13934 and ASTM D2261 standards. The results demonstrated that fiber type and matrix composition significantly influenced material performance, where cotton-based composites exhibited higher density and hardness, polyester-based composites showed greater flexibility, pineapple cotton composites achieved the highest tensile and tear strength, and banana polyester composites displayed superior ductility. Overall, the findings confirm that natural fiber–reinforced vegan leather produced using eco-friendly fabrication techniques possesses competitive physical and mechanical properties, making it a viable and sustainable alternative to conventional leather, with future work recommended to optimize fiber treatments, blending ratios, and long-term durability through advanced testing and life cycle assessment.